MODERASI BERAGAMA DALAM PERSPEKTIF PRAGMATISME PEIRCE DAN IMPLIKASINYA BAGI PENDIDIK KEAGAMAAN KATOLIK - Hironimus Bandur (STIPAS St. Sirilus Ruteng, 2022)
This paper seeks to answer the following three main questions. First, why is religious moderation being socialized intensively; second, how religious moderation is understood in the light of Charles Sander Peirce's philosophical pragmatism; and third, what are the implications of Peirce's thinking for the development of religious moderation for Catholic Education Teachers. To answer the questions referred to, the authors use library research. From the results of the analysis found the following answers. First, the socialization of religious moderation is carried out in the midst of the proliferation of chaotic religions, namely ethno-religiocentrism, island mentality, myopic understanding of religion towards humanity, radicalism in the world of education. Second, religious moderation inspired by Peirce's pragmatism refers to the balance between belief, investigation and meaning. Third, the implications of Peirce's pragmatism for the development of religious moderation in Catholic teachers is that the religioucity of Catholic teachers must uphold a balance between belief, investigation and its meanings for social transformation.